INCREASING THE STUDENTSâ€™ VOCABULARY MASTERY THROUGH CONSTRUCTIVISM PRINCIPLE IN THE FIFTH GRADE OF SDN ZAHA PROBOLINGGO - Zainuddin; Hamdani, Beny; Deviana, Avinda Mega (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2021)
This study focused on finding out whether â€œConstructivism Principleâ€ approach can be used to improve studentsâ€™ vocabulary mastery in the fifth grade of SDN ZAHA Probolinggo.This research involved twenty fifve students,thereare ten boys ang fifteen girls.The research instruments of this study consisted of obsevation guide in learning process, test, and given questionnaire. This study was a classroom action research. From the first cycle reflection result, some procedures and activities were revised accordingly.Steps include: (1)The students did the activities in groups made by the teacher which was not previously done in cycle 1; (2) different from cycle 1 which used â€œconstructivism principleâ€.In cycle 2 used Constructivism principle and some pictures related of tehnique used.The result from the action in cycle 2 was that the average score of students achieve 80,96.It can be concluded that used â€œConstructivism principleâ€ tehnique can improve the vocabulary mastery in the fifth grade of SDN ZAHA Probolinggo.